2012
DOI: 10.1002/pon.3169
|View full text |Cite
|
Sign up to set email alerts
|

Changes in supportive care needs after first‐line treatment for ovarian cancer: identifying care priorities and risk factors for future unmet needs

Abstract: Full title: Changes in supportive care needs after first-line treatment for ovarian cancer: identifying care priorities and risk factors for future unmet needs. Methods: 219 women with ovarian cancer were asked to complete a baseline survey 6-12 months after diagnosis then follow-up surveys every 6 months for up to 2 years. The validated SCNS-SF34 measured 34 needs across 5 domains. Logistic regression identified baseline variables associated with future needs.Results: At baseline, standardized median scores (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 29 publications
(67 reference statements)
7
58
3
2
Order By: Relevance
“…Our findings are consistent with other studies, which have found that younger women diagnosed with a malignancy are at particularly vulnerable to negative quality of life outcomes [10] [11]. Furthermore, evidence shows that even patients remote from treatment could benefit from continued support in regards to their emotional and psychological needs, and that women who have received chemotherapy are more likely to have unmet survivorship needs than women that have received other forms of treatment [12].…”
Section: Discussionsupporting
confidence: 82%
“…Our findings are consistent with other studies, which have found that younger women diagnosed with a malignancy are at particularly vulnerable to negative quality of life outcomes [10] [11]. Furthermore, evidence shows that even patients remote from treatment could benefit from continued support in regards to their emotional and psychological needs, and that women who have received chemotherapy are more likely to have unmet survivorship needs than women that have received other forms of treatment [12].…”
Section: Discussionsupporting
confidence: 82%
“…[6910111213141516] Few studies have investigated the supportive care needs of cancer patients in non-Western setting. [1718192021] While results of studies in non-Western countries reported that cancer patients have many unmet supportive needs, there remains several nuances between studies in the West and non-Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Primary needs in each of the common domains were: loss of previous functional ability (ADL); fatigue and pain (physical); being informed about self-care and having a professional contact with whom to discuss concerns (health system and informational); and illness-related fears and concerns about close others (psychological). Spiritual: Uncertainty about the future (13%) Beesley [22] Fears about the cancer spreading (25%)…”
Section: Prominent Specific Needsmentioning
confidence: 99%
“…The SCNS was the most commonly applied assessment -used in six studies [8, 20-22, 26, 37] -but even studies applying the SCNS used different variants of the tool (e.g., 34-item [22] versus 61-item [26] versions); classified needs in different ways (e.g., coding of some items as 'spiritual' [26] versus 'psychological' [21]); and applied different thresholds for identifying a need as 'unmet' (e.g., whether 'low' levels of need were considered to be unmet needs [37] or not [8]). As discussed above, measurement approaches and assumptions construct and constrain the needs that can be identified: this is most obviously the case in studies that purposively focussed on a single domain of need but even 'comprehensive' assessments like the SCNS arguably neglect some aspects of wellbeing (e.g., spiritual, cultural, and occupational needs).…”
Section: Assessment Of Unmet Needsmentioning
confidence: 99%